Exploring The Factors Influencing Knowledge Management Strategy in the European Shipbuilding Industry: A Pilot Study - Ni, Pengcheng; Kantola, Jussi (Journal of Knowledge Management Practice, 2025)
Knowledge is an important asset in shipbuilding. This paper aims to explore the key factors of knowledge management (KM) in European Shipbuilding to improve its strategic performance. This pilot study can form an important reference for knowledge management strategy implement in European shipbuilding. Data collected from project partners are used to test seven hypotheses by means of linear regression analysis, to identify the key factors of knowledge management strategy in European shipbuilding. This paper provides ideas for shipyards to consider when conducting knowledge management as part of the Smart European Shipbuilding (SEUS) project.
Keywords: knowledge management; European shipbuilding; knowledge management strategy